Psychometric characteristic of positive affect scale within the academic setting - Kartika Nur Fathiyah; Asmadi Alsa; Diana Setiyawati (Program Pascasarjana Universitas Negeri Yogyakarta & HEPI, 2019)
This analysis study is one of several stages that must be passed before testing the structural model. This study is initiated due to the limited information related to the measurement of the Positive Affect Scale within the academic settings. The research method used in this study was a quantitative method. It was done in among 724 students of state junior high schools in Sleman, Yogyakarta. The instrument development consisted of guideline arrangement, language feasibility testing, content validation through expert judgments, trials to measure the item discrimination index, item selection based on the item discrimination results, items representation for each indicator, and the construct validity test for the selected items. The testing of the measurement model used the data analysis techniques of Structural Equation Models (SEM) with the assistance of the AMOS program version of 21. The results of the study show that the validity analysis of the Positive Affect Scale within the academic setting was able to produce items that can reveal constructs or latent concepts appropriately.